Effect of Triazoles on Growth and Yield Attributes of Sesamum Indicum Linn. - Bora, K K (Annals of Arid Zone, 2016)
Paclobutrazol and XE-1019 reduced plant height, number of nodes, number of leaves, leaf area, dry weight of shoot, relative growth rate and net assimilation ratio but enhanced leaf area ratio in sesame. Treated plants had higher number of pods but low 1000-seed weight and significantly reduced yield due to poor seed selling.